Bedside and Community 50 Years of Contributions to the Health of Albertans by the University of Calgary - Stahnisch, Frank W.; Mansell, Diana; Larsson, Paula (University of Calgary Press, 2020)
The University of Calgary's innovative and collaborative approach to health care education is celebrated in an interdisciplinary collection. Bedside and Community is the inside story of fifty years of health care and health research at the University of Calgary. Drawing on the first-person accounts of researchers, administrators, faculty, and students along with archival research, and faculty histories, this collection celebrates the many significant contributions the University of Calgary has made to the health of Albertans. With contributions from the Cumming School of Medicine, the Faculty of Nursing, Faculty of Kinesiology, Faculty of Veterinary Medicine, Faculty of Environmental Design, Department of Psychology, and Indigenous Health Initiatives Bedside and Community is a truly collaborative history. Addressing the links between departments, the relationship between the university and the community, and evolving research and teaching methods, this book places the University of Calgary within a wider national context and shows how it has addressed the unique health needs of Southern Alberta. With a pioneering focus on primary care and commitment to interdisciplinary connections, the University of Calgary has made strides in health research, health education, and community outreach. Bedside and Community tells the story of a tradition of excellence that will light the way to future outreach and discovery.